Rapid qualitative analysis approach to stakeholder and client interviews to inform mobile-based HIV testing in the U.S. Deep South - Madeline C. Pratt; Oluwaseyi O. Isehunwa; Ingrid V. Bassett; Mirjam-Colette Kempf; Bretia Gordon; Lynn T. Matthews (BMC, 2023)
Abstract Background The severity of the HIV epidemic in the United States' rural South highlights geographic, socioeconomic, and racial disparities that disproportionately affect poor Black Americans. Approximately 16% of Alabamians living with HIV remain undiagnosed and just 37% of rural Alabamians have ever been tested for HIV. Methods We conducted in-depth interviews with 22 key stakeholders involved in HIV prevention, testing, treatment, or community health initiatives, and 10 adults living in rural communities across Alabama to explore HIV testing challenges and opportunities. We utilized a rapid qualitative analysis approach and engaged community partners for feedback and discussion. This analysis will inform the implementation of a mobile HIV testing service in rural Alabama. Results The following themes were identified: (1) Cultural norms, racism, poverty, and rurality impair access to healthcare. (2) Lack of sex education, low knowledge of HIV and perception of risk reinforce stigmas. (3) Messaging about "Undetectable = Untransmissible" (U = U) is not well understood in communities. (4) Community involvement may promote communication and trust between communities and testing advocates. (5) Novel testing strategies are acceptable and may diminish barriers. Conclusions Working with community "gatekeepers" may be a key strategy to understand and promote acceptability of interventions new to rural Alabama and ameliorate stigma within communities. The implementation of new HIV testing strategies requires building and maintaining relationships with advocates, especially faith-based leaders, who engage people across many demographics.